FACTORS AFFECTING THE INTENTION TO PURCHASE INSURANCE FOR CONSUMERS IN BANGKOK AND METROPOLITAN REGION - Sannikornpap, Trirat; Punpugdee, Nuttapon (Journal of MCU Nakhondhat, 2022)
The objectives of this research article were to: 1. personal factors of consumers in Bangkok and vicinities of life insurance purchase decision, 2. environmental factors of consumers’ intent to purchase life insurance in Bangkok and vicinities, 3. consumers’ intention to purchase life insurance process in Bangkok and its vicinity is classified by personal factors, 4. the process of intending to purchase life insurance for consumers in Bangkok and its vicinity is classified by personal factors, 5. the relationship between environmental factors and the process of intending to purchase life insurance for consumers in Bangkok and its vicinities. This was explanatory research using a questionnaire as a tool to collect data. The population was 400 consumers in Bangkok and surrounding provinces who purchased life insurance. Data were analyzed using descriptive and inferential statistics. The results of consumer research are mostly female, aged 25-33 years, with bachelor’s degrees, single status, income between 15,001-30,000 baht and working as a private employee and giving importance to the overall purchase intention of life insurance at a high level when considering each aspect, namely financial status, followed by service, relationship with the company, and behavioral aspects, respectively. Product external environment in relation to family and sides respectively consumers’ level of intent to buy life insurance in Bangkok and vicinities overall, it’s at a very intentional level. When considering each aspect, it was found that it was at a high level of intention. The hypothesis testing results revealed that the gender consumer monthly income and different occupations have different intentions to purchase life insurance for consumers in Bangkok and its vicinities. The age consumer education level and different marital status. They have the same intention to purchase life insurance for consumers in Bangkok and its vicinities. The statistical significance at the 0.05 level and the environmental factors were behavior, service, and external environment. It is a predictor that has an influence on the behavior of consumers in the Bangkok Metropolitan Region and the purchasing intention of life insurance.